Analysis of Topic Shift Used by Host in The David Rubenstein Show - Salsabila, Naila Hana; Farida, Alief Noor (Journal of English Language and Education, 2026)
In talk shows, the host's management of conversation topics plays a very important role in improving the quality of communication. However, research on topic management in talk shows is still limited because most previous studies have focused on other aspects of talk shows. To fill this gap, this study aims to identify the topic shifts used by hosts in talk shows based on the typology of topic shifts proposed by Crow (1983). The research data was taken from a YouTube video titled “The David Rubenstein Show: Maria Sharapova,” which was then analyzed using a descriptive qualitative approach. The results show that the host used all types of topic shifts with a total of 35 utterances, and the most frequently used were topic initiation and topic shading. Therefore, this study reinforces that hosts in talk shows have a major influence on the flow of interaction through the use of topic shifts.